Answer:
![y =- (3)/(2)x - 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p1vg08sfmhc1z4jl48rff6t1jztz91affe.png)
Explanation:
Given equation of line is:
2x-3y=13
We will convert the equation of line in point-slope form to find the slope of the line
Let
m_1 be the slope of the line
So,
2x-3y=13
-3y= -2x+13
Dividing both sides by -3
(-3y)/(-3)=(-2x)/(-3)+13/(-3)
y=(2/3)x-13/3
The co-efficient of x is the slope of the line.
So,
m_1=2/3
Let
m_2 be the slope of second line
As we know that product of slopes of two perpendicular line is -1
m_1 m_2= -1
2/3*m_2= -1
m_2= -1*3/2
m_2= -3/2
So m2 is the slope of the line perpendicular to given line.
The standard equation of a line is
y=mx+b
To find the equation of line through (-6,5), put the point and slope in the given form and solve for b
5= -3/2 (-6)+b
5=18/2+b
5=9+b
b=5-9
b= -4
Putting the values of slope and b, we get
![y =- (3)/(2)x - 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p1vg08sfmhc1z4jl48rff6t1jztz91affe.png)